O excursionismo e o gosto pela natureza - Juodinis, Gisele (2006)
Through a dense description, it was attempted to understand the values involved in directing the traveler s look who is attached to the taste for the nature. The signs which interest the people on their trips have a preset value in this modern society which are important for the investigation of it. This way, it was attempted to read the symbolic games which were hidden behind the preferences of a determined segment of the bourgeois society, sense and implicit meanings in the emotions of the excursionist/ mountain climber s leisure practice. Having the theoretical support of Pierre Bourdieu s ideas of habitus and life style and also relating the historical way modern society has gone through and its relationship with the natural world, we see that nowadays, there is a disposition to value this world. While the progress of an urban-industrial society sees the necessity of revising its ideals before facing a global ecological breakdown, men are continuously rethinking ways of doing and being. The contact with nature these days is going through modern and civilized rituals which are expressed as values in the symbolic game of this society